IMPLEMENTASI TATA KELOLA BERBASIS PARTISIPASI GURU DALAM PENGEMBANGAN PROGRAM SEKOLAH DI SDN BAHAGIA 01 - Fira Atsaqifa; Fara Diba Catur Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the implementation of school governance based on teacher participation within the framework of School-Based Management (SBM) at SDN Bahagia 01. The research is grounded in the problem of limited teacher involvement in decision-making processes, which may hinder school effectiveness and sustainability of educational programs. The purpose of this study is to describe the level of teacher participation, identify governance patterns, and analyze the implications of participatory governance for school quality improvement. A qualitative descriptive approach was employed, involving the school principal, teachers, and educational staff as research subjects. Data were collected through participatory observation, semi-structured in-depth interviews, and document analysis. Data analysis followed the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing, with data validity ensured through source and technique triangulation. The findings reveal that teacher participation at SDN Bahagia 01 is highly evident in the planning and implementation stages, and moderately to highly present in program evaluation. Participatory leadership by the principal fosters collaboration, strengthens teachers’ sense of ownership and responsibility, and encourages instructional innovation. Overall, the study concludes that school governance based on active teacher participation contributes significantly to the effectiveness of School-Based Management and supports continuous improvement in school quality.